Evaluating the implementation of iron supplementation to prevent stunting and anemia: A qualitative case study at the Benu-Benua Community Health Center, Kendari, Indonesia - Bahar, Hartati; Karisma Dewi, Febri; Lestari, Hariati; Albar Kalza, Lade (CORE JOURNAL, 2025)
Previous studies on iron supplementation programs have largely focused on policy outcomes and national strategies, often overlooking the implementation dynamics at the primary healthcare level. This study addresses this gap by evaluating the implementation of the Iron Supplement Tablets (TTD) program at the Benu-Benua Health Center in Kendari City, Indonesia. Using a qualitative case study design, data were collected through in-depth interviews, observation, recordings, and documentation involving nine purposively selected informants, including health center staff and beneficiaries. Thematic content analysis was applied through stages of data reduction, presentation, and conclusion drawing. The findings show that although inputs such as human resources, funding from the Health Operational Assistance (BOK), and educational media are available, no specific training was provided to program implementers. SOPs exist but are not visibly posted, and coordination between stakeholders remains suboptimal. The process revealed that TTD planning and implementation were based on standard targets, but monitoring and recording were weak, leading to challenges in tracking outcomes. Output analysis showed that while pregnant women generally received TTD, distribution among adolescents was inconsistent, and consumption compliance was low. These results underscore the need for improved training, monitoring mechanisms, and cross-sectoral collaboration. Strengthening these areas is crucial for enhancing the impact of iron supplementation programs and supporting public health efforts to reduce stunting and anemia.